A New Framework to Incorporate High‐Latitude Input for Mesoscale Electrodynamics. Issue 1 (21st January 2020) - Ozturk, D. S.; Meng, X.; Verkhoglyadova, O. P.; Varney, R. H.; Reimer, A. S.; Semeter, J. L.
Abstract: Global circulation models (GCMs) for the ionosphere‐thermosphere system traditionally use empirical models to specify upper boundary conditions to represent solar wind and magnetospheric drivers. However, the magnetosphere, ionosphere, and thermosphere systems are coupled on different spatial and temporal scales. During increased levels of geomagnetic activity, these empirical models can't resolve dynamic electric field variability ( < 500 km, < 15 min) because of their statistical nature and/or low spatial and temporal resolutions. This results in an underestimation of energy input to the ionosphere, causing disagreements between model results and observations. This paper introduces a new framework to incorporate dynamic electric fields into GCMs: High‐latitude Input for Mesoscale Electrodynamics (HIME). As a demonstration HIME uses the Poker Flat Incoherent Scatter Radar (PFISR) electric field estimates during an experiment on 2 March 2017. The electric potentials were calculated using the PFISR estimates and merged with a global empirical model of electric potential. A set of high‐latitude electric potential drivers were used to drive the University of Michigan Global Ionosphere Thermosphere Model (GITM) to understand the effects of driving at different scales. Data versus model comparisons for ion temperature, electron temperature, and electron density are provided along the PFISR beams. The ion convection velocities and neutral winds at the PFISR location are compared with the PFISR and Scanning Doppler Imager data. The effects of different multiscale drivers are investigated. The results showed that energy deposited by HIME‐driven simulations was locally larger by approximately an order of magnitude compared to the empirical model‐driven results. Key Points: For the first time local, dynamic, 2‐D electric field estimates are merged with a global empirical model Local mesoscale electric field variability is successfully communicated to GITM The energy deposited locally in HIME‐driven simulations is higher compared to Weimer‐driven simulations